The Silent Zero in Aryabhatiya: Aryabhata’s Mathematical Vision in Gupta India - Dey, Kishore (Information Research Communications, 2026)
Background Aryabhata, the renowned mathematician and astronomer of the Gupta Golden Age, composed the Aryabhatiya in 499 CE at the age of 23. The text, consisting of 121 stanzas in four chapters: Gitika-pada, Ganita-pada, Kalakriya-pada, and Gola-pada presents a synthesis of mathematics, astronomy, and calendrical science. Methodology It includes definitions of time units, astronomical tables, planetary positions, and rules of calculation, introducing innovative methods such as trigonometric functions, approximation of π, and indeterminate equations. Aryabhata’s mathematical originality lies in the positional number system with an implied zero, expressed through alphabetical notation, which operated as a “silent zero” shaping later mathematical traditions. Results His precise value of π, trigonometric sine tables, and kuttaka method for indeterminate equations stand as pioneering contributions. In astronomy, Aryabhata explained the rotation of the Earth, the fixed position of stars, the concept of continuous time (anadi, ananta), cyclical yugas and kalpas, planetary motions, epicycles, and eclipses. His calculation of the sidereal rotation of the Earth (23 hr 56 min 4.1 sec) closely matches modern values. Comparisons with the Surya-siddhanta highlight both differences and continuities, particularly regarding planetary cycles, time divisions, and eclipse phenomena. Conclusion The study emphasizes Aryabhata’s intellectual vision within the Gupta period, where mathematical abstraction and astronomical precision were integrated into a coherent system. His legacy influenced subsequent scholars like Bhāskara I and extended through Arabic and European traditions, marking the Aryabhatiya as a milestone in the global history of mathematics and astronomy.
Keywords: Aryabhata; Aryabhatiya; Gupta period; Silent zero; π; Trigonometry; Kuttaka; Astronomy; Surya-siddhanta.